EGFR mutant-specific immunohistochemistry has high specificity and sensitivity for detecting targeted activating EGFR mutations in lung adenocarcinoma. Issue 9 (11th June 2013) - Cooper, W A; Yu, B; Yip, P Y; Ng, C C; Lum, T; Farzin, M; Trent, R J; Mercorella, B; Clarkson, A; Kohonen-Corish, M R J; Horvath, L G; Kench, J G; et al.
Abstract : Aim: We assessed the diagnostic accuracy of epidermal growth factor receptor ( EGFR ) mutant-specific antibodies for detecting two common activating EGFR mutations. Methods: Immunohistochemical expression of mutation-specific antibodies against EGFR exon 19 deletion E746-A750 ((c.2235_2249del15 or c.2236_2250del15, p. Glu746_Ala750del) and exon 21 L858R point mutation (c.2573T>G, p.Leu858Arg) were assessed in a cohort of 204 resected early stage node negative lung adenocarcinomas, and protein expression was compared with DNA analysis results from mass spectrometry analysis. Results: Of seven cases with L858R point mutation, six were positive by immunohistochemistry (IHC). There were three false positive cases using L858R IHC (sensitivity 85.7%, specificity 98.5%, positive predictive value 66.7%, negative predictive value 99.5%). All seven E746-A750 exon 19 deletions identified by mutation analysis were positive by IHC. Four additional cases were positive for exon 19 IHC but negative by mutation analysis. The sensitivity of exon 19 IHC for E746-A750 was 100%, specificity 98.0%, positive predictive value 63.6% and negative predictive value 100%. Conclusions: Mutant-specific EGFR IHC has good specificity and sensitivity for identifying targeted activating EGFR mutations. Although inferior to molecular genetic analysis of the EGFR gene, IHC is highly specific and sensitive for the targeted EGFR mutations. The antibodies are likely to be of clinical value in cases where limited tumour material is available, or in situations where molecular genetic analysis is not readily available.